STUDI GANGGUAN FASA KE TANAH PADA GI YANG MENDAPAT SUPLAI MELALUI KOMBINASI SUTT DAN KABEL TANAH - Wahyudi SN; Tony Koerniawan; Pramudani Wanda Saraswati (Sekolah Tinggi Teknik - PLN, 2016)
Electrical energy is generated in power station and transmited to the consumers trough transmission lines and distribution lines. Transmission lines connected a power station and a substation and can connected substation and a substation. Transmission lines can be overhead line or underground cable. Sometimes the line consists of overhead lines combined with underground cable lines. Connection between overhead lines and underground cable in done in transition station. If a line to ground fault happen there will be a gradient voltage in the area of transition station and in thesubstation. In this papper will be studied the gradient voltage in the transition station related the length of underground cable line.